1991
DOI: 10.1128/iai.59.4.1352-1358.1991
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology of Citrobacter diversus neonatal meningitis: comparative studies in an infant mouse model

Abstract: Citrobacter diversus is a cause of devastating neonatal meningitis, with illness characterized by formation of multiple brain abscesses. We developed an infant mouse intracranial inoculation model to evaluate the pathophysiology of C. diversus neonatal infections. Eighteen of 26 strains inoculated intracranially at a dose of ca. 3.3 x 103 CFU caused >50% mortality in 2-day-old mice. No correlation was seen between the epidemiologic characteristics of a strain and its rate of mortality. When seven C. diversus i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Previously research made use of infant mouse models to study the pathogenicity of C. koseri (Soriano et al, 1991). Some in vitro studies have shown that C. koseri is able to invade and replicate inside human U937 macrophages and human brain microvascular endothelial cells (Badger et al, 1999; Townsend et al, 2003).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously research made use of infant mouse models to study the pathogenicity of C. koseri (Soriano et al, 1991). Some in vitro studies have shown that C. koseri is able to invade and replicate inside human U937 macrophages and human brain microvascular endothelial cells (Badger et al, 1999; Townsend et al, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…To test our hypothesis, we generated a mutant strain that lacks all HPI clusters (ΔHPI:chlR) in C. koseri TBCP-5362. As previously described, two animal models were used in our study: 2-day-old SD rats and 18-day-old BALB/c mice (Soriano et al, 1991; Liu et al, 2019). Three groups of each animal model were inoculated with wild-type or ΔHPI mutants of C. koseri TBCP-5362 (∼5 × 10 5 colony forming units (CFUs) for 2-day-old SD rats and ∼1 × 10 7 CFUs for 18-day-old BALB/c mice).…”
Section: Resultsmentioning
confidence: 99%
“…Abscesses from C. koseri typically lack a fibrous capsule. Moreover, the bacteria invade meninges and ependyma, with subsequent parenchymal disruption and hydrocephalus [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…C. koseri is an occasional inhabitant of human and animal intestines and of soil, water, sewage, and food 4. Although disease caused by this organism has not previously been reported in domestic animals, the bacteremia, meningitis, and multifocal brain abscessation described in humans has been experimentally reproduced in a murine model 14. Although it is not clear why C. koseri infection became established in these two puppies, immune naivety or intercurrent immunosuppression may have been contributory factors.…”
mentioning
confidence: 99%